2002
DOI: 10.2133/dmpk.17.522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Serum Albumin and Liver Cytosol on CYP2C9- and CYP3A4-mediated Drug Metabolism

Abstract: To investigate whether the free-drug theory is accurate in that only unbound drug is available for drug metabolism or enzyme inhibition. The effect of addition of rat liver cytosol to an in vitro system using human liver microsomes was examined by measuring the catalytic activities of CYP2C9 (tolbutamide and diclofenac) and CYP3A4 (terfenadine). And, the results were compared with those obtained when human serum albumin (HSA) was added to microsomes as far as unbound drug concentrations were concerned. After a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…13,38,39 Related to this, specific in vitro studies with liver microsomes also point to proteinfacilitated metabolism because the values of K m were often smaller in the presence of AL as compared with the control. 14,15 Because liver microsomes and membranes of hepatocytes have a similar composition of lipids to which the AL-drug complex may aggregate, 50,51 it might at least be argued that the AL-drug complex presents a greater nonspecific binding as compared with the free drug molecule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,38,39 Related to this, specific in vitro studies with liver microsomes also point to proteinfacilitated metabolism because the values of K m were often smaller in the presence of AL as compared with the control. 14,15 Because liver microsomes and membranes of hepatocytes have a similar composition of lipids to which the AL-drug complex may aggregate, 50,51 it might at least be argued that the AL-drug complex presents a greater nonspecific binding as compared with the free drug molecule.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Burczynski et al 13 observed that the CL of palmitate, a compound highly bound to albumin (AL), was significantly larger in the presence of AL in incubations as compared with when no AL was added, which are in accordance with Blanchard et al 5 Related to this, other studies seem to indicate that adding AL in the incubation medium may result in greater nonspecific binding of the AL-drug complex as compared with controls because smaller Michaelis-Menten affinity constant (K m ) values were observed. 14,15 Thus, these observations might result in whole-liver fu (fu liver ) significantly larger than fu p under in vivo conditions, and hence explain why the consideration of protein binding inside the whole-liver compartment could be important for more accurate IVIVE calculations of drugs eliminated principally by metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The microsomal binding of S-mephenytoin, testosterone, nifedipine, and quinidine was performed using the method of microfiltration as has been described previously (Carlile et al, 1999). Microsomal binding data for the other substrates were obtained from published literature (Carlile et al, 1999;Obach, 1999;Baba et al, 2002;Margolis and Obach, 2003), and the fraction unbound in microsomes (fu mic ) was calculated using eq. 1, where K a represents the affinity constant for the drug-protein interaction and [P] represents the microsomal protein concentration.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that estimation of K i values of CYP2C9 inhibitors is affected by protein binding of these inhibitors in enzyme sources. 16,17) Baba et al 16) reported that an apparent K i value (0.188 µM) of miconazole for HLMs-mediated tolbutamide 4-hydroxylation was largely different from the K i, u value (0.0024 µM) due to a very low unbound fraction (0.95-1.88%) of miconazole in an incubation mixture containing HLMs. If iguratimod binds to proteins of HLMs and rCYP2C9s, it is possible to overestimate the apparent K i values of iguratimod.…”
Section: Discussionmentioning
confidence: 99%